Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - Review Exercises - Page 152: 18



Work Step by Step

The middlepoint between $(-2,-3)$ and $(4,-10)$ is the center of the circle: $\frac{(-2,-3)+(4,-10)}{2}=(1,-\frac{13}{2})$, that is: $h=1$, $k=-\frac{13}{2}$ The distance from the center to an endpoint is the radius: $r=\sqrt {[1-(-2)]^2+[-\frac{13}{2}-(-3)]^2}=\sqrt {9+\frac{49}{4}}=\frac{\sqrt {85}}{2}$ Equation of a circle: $(x−h)^2+(y−k)^2=r^2$ (standard form) $(x-1)^2+[y-(-\frac{13}{2})]^2=(\frac{\sqrt {85}}{2})^2$ $(x-1)^2+(y+\frac{13}{2})^2=\frac{85}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.